2011
DOI: 10.1038/npp.2011.97
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Increase in Hypothalamic Arginine Vasopressin Gene Expression During Protracted Withdrawal from Chronic Escalating-Dose Cocaine in Rodents

Abstract: Arginine vasopressin (AVP) from the paraventricular nucleus (PVN) of hypothalamus has important roles in regulation of the hypothalamic-pituitary-adrenal (HPA) axis and stress-related behaviors during chronic stress. It is unknown, however, whether AVP in the PVN is involved in the modulation of HPA activity after chronic cocaine exposure. Here, we examined the gene expression alterations of AVP in the hypothalamus, and V1b receptor and pro-opiomelanocortin (POMC) in the anterior pituitary, as well as HPA horm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 53 publications
1
33
0
Order By: Relevance
“…Of interest, abnormal HPA activity in response to the dexamethasone test during alcohol withdrawal has also been found in humans (Hundt et al, 2001). This is further supported by the findings that an increase in AVP mRNA, but not CRF mRNA, was found in mice and rats during more than 2-week alcohol or cocaine withdrawal with HPA abnormal activation (Zhou et al, 2011b;Pang et al, 2013) (see more details in Section II). However, few studies have specifically addressed the involvement of AVP and V1b receptor systems in relapse-like drinking and the HPA modulation after chronic withdrawal from long-term alcohol exposure in rodent models, though AVP is a potent modulator of brain stress responsive systems and HPA axis.…”
Section: Section I Stress Responsive Hypothalamicepituitaryeadrenal mentioning
confidence: 70%
See 2 more Smart Citations
“…Of interest, abnormal HPA activity in response to the dexamethasone test during alcohol withdrawal has also been found in humans (Hundt et al, 2001). This is further supported by the findings that an increase in AVP mRNA, but not CRF mRNA, was found in mice and rats during more than 2-week alcohol or cocaine withdrawal with HPA abnormal activation (Zhou et al, 2011b;Pang et al, 2013) (see more details in Section II). However, few studies have specifically addressed the involvement of AVP and V1b receptor systems in relapse-like drinking and the HPA modulation after chronic withdrawal from long-term alcohol exposure in rodent models, though AVP is a potent modulator of brain stress responsive systems and HPA axis.…”
Section: Section I Stress Responsive Hypothalamicepituitaryeadrenal mentioning
confidence: 70%
“…The HPA hormones in response to chronic cocaine show a significant attenuation compared to the acute effects, indicating tolerance of HPA activity to chronic cocaine (Zhou et al, 1996a), as also found in cocaine dependent men (Mendelson et al, 1998). In early (1e2 days) cocaine withdrawal, there is a slight, but significant, increase in plasma ACTH levels at the nadir time point of circadian cycle (Zhou et al, 1996a(Zhou et al, , 2003a(Zhou et al, , 2003b(Zhou et al, , 2011b. During 14-day protracted withdrawal from chronic escalating-dose binge cocaine, there was a slight and persistent elevation of ACTH secretion, mediated through increased AVP activity in the paraventricular nucleus (Zhou et al, 2011b).…”
Section: Section I Stress Responsive Hypothalamicepituitaryeadrenal mentioning
confidence: 91%
See 1 more Smart Citation
“…In early (1-2 day) cocaine withdrawal, there is a slight, but significant, increase in HPA hormones (68,69). During protracted withdrawal from chronic escalating-dose (but not steady-dose) "binge" cocaine, enhanced AVP/V1b expression was associated with persistent elevations of HPA activity (56).…”
Section: Stress Systems In the Neurobiology Of Addictionsmentioning
confidence: 99%
“…Both CRF-R1 and AVP-V1b receptors are located on corticotropes in the anterior pituitary and drive the processing and release of ACTH and β-EP from the pro-opiomelanocortin (POMC) peptide, of particular interest for the field of addictive diseases (55,56). Endogenous opioids are critical in the control of the HPA axis.…”
Section: Stress Systems In the Neurobiology Of Addictionsmentioning
confidence: 99%